The Role of Incentives Structure on Employee Performance in the Sierra Leone Banking Sector - Mohamed Sesay (International Journal of Management, Accounting and Economics)
A study explores how incentive structures with monetary and non-monetary rewards influence Sierra Leone's banking sector employee performance and the effect of management and employee commitment as moderating or mediating factors. A survey design based on quantitative methods used self-administered questionnaires distributed to 203 bank employees working in seven institutions. Smart PLS 4 with PLS-SEM was used to perform the model's validity tests, reliability, and prediction assessment. The research shows monetary incentives negatively influenced performance (β = -0.185, p = 0.004) while non-monetary incentives demonstrated a positive impact (β = 0.175, p = 0.008) with more significant effects. Management commitment is the primary moderating factor that enhances how non-monetary incentives improve employee performance (β = 0.320, p = 0.000). The research showed that employee commitment failed to serve as a pathway through which financial and non-financial incentives impacted performance levels (p>0.05). Thus, the organization requires supplementary workplace backing systems. The model effectively predicts 67.5% (R² = 0.675) of variations in employee performance rates. Financial institutions must use hybrid monetary and non-monetary incentive programs since monetary rewards provide immediate motivation. In contrast, recognition, career development, and flexible work options enhance staff motivation and dedication. Hence, this paper contributes significantly to the existing literature by developing and testing a model highlighting how Banks should improve staff satisfaction, lower employee turnover rates, and yield superior organizational performance by linking reward systems to business targets and workforce requirements.